Immortal diamond: versions of selfhood in Charles Dickens, Thomas Carlyle, Robert Browning and George Macdonald - Ward, Heather Patricia (1981)
The aim of this thesis is to explore the versions of selfhood found in the works of Charles Dickens, Thomas Carlyle, Robert Browning and George MacDonald in relation to patristic theological anthropology rather than to modern psychology. It sets the view of selfhood of these authors within the context of the English Christian and literary heritage and of their own period.